AWÍR SÓYLEW KEMShILIGI BAR BALALARDÍŃ KOMMUNIKATIV KÓNLIKPELERIN TEKSERIW USÍLLARÍ - Ajimova, Z.G. (ILIM hám JÁMIYET, 2025)
The article examines methods for determining the level of underdeveloped communication skills in children with alalia, a speech disorder. A program has been developed to assess the communication skills of children with alalia.